Predictors of uncontrolled hypertension and antihypertensive medication nonadherence - Morgado, Manuel (2010)
Background: Although hypertension is, in most cases, a controllable major risk factor in the development of cardiovascular disease, studies have demonstrated that hypertension remains poorly controlled in Portugal. Our aim was to evaluate the covariates associated with poor blood pressure (BP) control in a Portuguese hypertensive population. Patients and Results: We conducted a cross-sectional survey in a hospital hypertension outpatient clinic, located in the Eastern Central Region of Portugal. Patients attending the clinic from July to September 2009 were asked to participate in a structured interview including medication adherence and knowledge about hypertension. Eligible participants were all adults aged 18 or over with an established diagnosis of arterial hypertension and had been on antihypertensive drug treatment for at least 6 months. Exclusion criteria were dementia, pregnancy, and breastfeeding. Detailed clinical information was prospectively obtained from medical records. A total of 197 patients meeting the inclusion criteria and consenting to participate completed the interview. Of these, only 33.0% had their BP controlled according to the JNC 7 guidelines. Logistic regression analysis revealed three independent predictors of poor BP control: living alone (OR = 5.3, P = 0.004), medication nonadherence (OR = 4.8, P < 0.001), and diabetes (OR = 4.4, P = 0.011). Predictors of medication nonadherence were: unawareness of target BP values (OR = 3.7, P < 0.001), a report of drug side effects (OR = 3.7, P = 0.002), lack of BP monitoring (OR = 2.5, P = 0.015) and unawareness of medication indications (OR = 2.4, P = 0.021), and of hypertension risks (OR = 2.1, P = 0.026). Conclusions: Poor medication adherence, lack of information about hypertension, and side effects should be considered as possible underlying causes of uncontrolled BP and must be addressed in any intervention aimed to improve BP control.